2010
DOI: 10.1246/cl.2010.354
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid Eco-friendly Synthesis of Cubic Octamethylsilsesquioxane Using Microwave Irradiation

Abstract: Octamethylsilsesquioxane (Me 8 Si 8 O 12 ) having a cage structure was rapidly prepared by means of microwave-assisted solgel reaction of methyltrimethoxysilane as a trifunctional alkoxysilane with an aqueous basic solution in diglyme as a solvent. Moreover, octamethylsilsesquioxane was obtained as cubic particles in a good yield. Cubic octamethylsilsesquioxane could be formed under microwave irradiation owing to the formation of micelles which are organized by eight methyltrimethoxysilane molecules in diglyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The remaining peaks are produced by the rhombohedral crystal structure of POSS molecules (14,15). These results indicated that the product had good crystallinity and the structure was high symmetry (16).…”
Section: Resultsmentioning
confidence: 91%
“…The remaining peaks are produced by the rhombohedral crystal structure of POSS molecules (14,15). These results indicated that the product had good crystallinity and the structure was high symmetry (16).…”
Section: Resultsmentioning
confidence: 91%
“…The high condensation degree of MTMS-derived powder (98%) suggests a densely packed network in which the methyl group fits well, as also indicated by the ability of methylated silica to crystallize. 61 , 62 Interestingly, the addition of terminal methyl groups in BMDESE-derived material as compared to BTESE-derived powder increased the rotational freedom of molecular segments but did not increase the condensation degree. The methyl groups did not preferentially replace noncondensed hydroxyl groups, suggesting that the hydroxyl groups had little freedom to rearrange or that the ethylene bridges introduced too much spacing to enable higher condensation degrees.…”
Section: Resultsmentioning
confidence: 99%
“…This method allows rapid and direct heating of the reaction media. In most cases, microwave can dramatically reduce reaction times and increase product yields . In our previous research, we found that the anionic hydrogen‐transfer polymerization of AAm utilizing microwave irradiation easily provides poly( β ‐alanine) as a resulting polymer in a short space of time .…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, microwave can dramatically reduce reaction times and increase product yields. [20][21][22][23] In our previous research, we found that the anionic hydrogen-transfer polymerization of AAm utilizing microwave irradiation easily provides poly(β-alanine) as a resulting polymer in a short space of time. 24 When N-substituted amides with low reactivity as described above are polymerized, the anionic polymerization of N-substituted amides proceeds via a hydrogen-transfer process when using microwave irradiation.…”
mentioning
confidence: 99%